(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
To understand Black Feminist thinking, it is important to explore the context out of which it emerges. We will analyze the evolution of Black Feminist consciousness and thought in the 1930s to contemporary time, since the struggle for black women’s liberation which emerged in the mid-1960s is a construction of both intellectual and activist tradition during slavery and during the anti-slavery movement. This course will also be an interpretative analysis of the work and thought produced by a range of leading black women writers, scholars and intellectuals in everyday and alternative locations for knowledge production. For purposes of this paper, Black Women encompasses all women of descent/heritage in the diaspora. These women all rely upon the notion that issues of race, gender, sexuality and social class are central, rather than peripheral to any history, analysis or assessment of life. During the course we will outline the basic principles and practices of Black Feminism, contextualize the emergence of contemporary feminist work in historical perspective and also examine the written and spoken texts of nineteenth century feminist foremothers. We will identify and characterize the major issues which black feminists address as well as the various forms of resistance to social structures. Black women will be viewed as producers of knowledge and as transforming agents. We will study the works and contributions of early feminists as well as later and contemporary scholars and activists.